2023
DOI: 10.26599/jac.2023.9220707
|View full text |Cite
|
Sign up to set email alerts
|

Successful preparation of BaCo 0.5Fe 0.5O 3– δ cathode oxide by rapidly cooling allowing for high-performance proton-conducting solid oxide fuel cells

Abstract: A pure phase BaCo 0.5 Fe 0.5 O 3-δ (BCF), which cannot be obtained before, is successfully prepared in this study by using the calcination method with a rapid cooling procedure. The successful preparation of BCF allows the evaluation of this material as a cathode for proton-conducting solid oxide fuel cells (H-SOFCs) for the first time. An H-SOFC using the BCF cathode achieves an encouraging fuel cell performance of 2012 mW•cm -2 at 700 , two ℃ -fold higher than that of a similar cell using the classical high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 62 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…The solution is then heated in an electric furnace at 250 °C until the spontaneous combustion process occurs, resulting in BCF precursor powders, which are calcined at 1000 °C for 3 h. Finally, the as-calcined BCF powders are cooled to room temperature to yield S-BCF and R-BCF samples by cooling the BCF precursor powders with a setting cooling rate of 3 and 300 °C min −1 , respectively. 49 Note that the chemicals used in this work are all analytical reagents (AR) and purchased from Sinopharm Chemical Reagent Co., Ltd, while the manufacturers of other chemicals or materials used for electrochemical performance measurements are summarized in Table S1 †…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solution is then heated in an electric furnace at 250 °C until the spontaneous combustion process occurs, resulting in BCF precursor powders, which are calcined at 1000 °C for 3 h. Finally, the as-calcined BCF powders are cooled to room temperature to yield S-BCF and R-BCF samples by cooling the BCF precursor powders with a setting cooling rate of 3 and 300 °C min −1 , respectively. 49 Note that the chemicals used in this work are all analytical reagents (AR) and purchased from Sinopharm Chemical Reagent Co., Ltd, while the manufacturers of other chemicals or materials used for electrochemical performance measurements are summarized in Table S1 †…”
Section: Methodsmentioning
confidence: 99%
“…However, Yin et al found that the iron doped perovskite oxide BaCo 0.5 Fe 0.5 O 3− δ (BCF) material yielded at 1000 °C, a solid solution of BaCoO 3 and BaFeO 3 , was transformed into a mixture of the perovskite-type BCF phase and BaCoO 2.6 phase at room temperature, but could be well-kept by a rapid cooling treatment after calcination at 1000 °C, leading to improved solid oxide fuel cell performance. 49 Till now, perovskite oxide BCF materials have not yet been utilized as cathodes in ZABs, which is possibly ascribed to their synthesis difficulty. The choice of oxygen electrocatalysts is therefore limited.…”
Section: Introductionmentioning
confidence: 99%
“…LSSF material was synthesized by a sol–gel method, 54 using stoichiometric amounts of La 2 O 3 , SrCO 3 , Sc 2 O 3 , and Fe(NO 3 ) 3 as the starting materials. The metal oxides and metal carbonates were dissolved in nitric acid.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Alternatively, this technology can be operated in reversible mode in solid oxide fuel cells (SOFCs) to produce electricity with the generated fuel. 3–7 This is of great importance since they can be employed as an energy management strategy for the mismatch between the energy supply and demand, due to the increasing intermittent renewable energy sources such as solar and wind. However, one of the critical issues of commercialization of this technology is the durability of SOECs at high current density.…”
Section: Introductionmentioning
confidence: 99%